CAHAYA AL-QUR’AN UNTUK MANUSIA MODERN - Masduki A. Sayuti (Universitas Islam Depok, 2023)
The Prophet had locked the position of the Al-Quran by saying that the Al-Quran is shalihun likulli Zaman wa eat. Then why is it that religious and human life today, especially in Muslim society, seems to be kept away from those things that are miraculous?. Humans are the best creatures created by God. Humans in the editorial verses of the Koran have several terms, such as al nas, al ins, al insan, and Bani Adam. From these terms some of the meanings can be revealed which provide information about the origin of human creation and its behavior. Human existence in general acts as a servant of Allah (Abd.Allah) and as a protector or prosperous on the surface of the earth (khalifah Allah). The modern era is marked by various discoveries in the scientific field. The development of science in modern times has actually been pioneered since the Renaissance era. The beginning of a new era was marked by Descartes' great effort to give philosophy a new structure. Philosophy developed not during the Renaissance, but later in the later era (Modern Age). Examining and understanding the holy Quran, which is shalihun likulli Zaman wa Makan, is a term coined 14 centuries ago, meaning that it contains a deep message that the Quran will always be in accordance with the conditions of the era and place.